2004
DOI: 10.1093/jac/dkh163
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in broad-spectrum antimicrobial use associated with no improvement in hospital antibiogram

Abstract: Implementation of an antibiotic management programme resulted in substantial reductions in both broad-spectrum and total antimicrobial consumption without having a significant impact on antibiotic susceptibilities of common Gram-negative microorganisms within the institution. The changes in MRSA rate in the non-ICU and ICU settings may reflect infection control measures that were in place during the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 21 publications
1
63
2
6
Order By: Relevance
“…S1 in the supplemental material). Of note, only one of six studies applied antifungal restriction in their formulary (Table 1) (30).…”
Section: Resultsmentioning
confidence: 99%
“…S1 in the supplemental material). Of note, only one of six studies applied antifungal restriction in their formulary (Table 1) (30).…”
Section: Resultsmentioning
confidence: 99%
“…19 Studies of the effect of reducing antimicrobial use on the incidence of antimicrobial resistance have yielded various results. 12,14,20 In 1990, Mouton et al 21 reported a correlation of methicillin resistance in coagulase-negative staphylococci and use of (flu)cloxacillin, cephalosporins and gentamicin. Other studies have reported correlations in use of antimicrobials and development of resistance in S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…At a 731-bed teaching hospital in North Carolina, a program incorporating restriction and review was implemented (33). Restricted antimicrobials required prior approval by an infectious diseases physician, whereas controlled agents were freely dispensed but reviewed within 48 h by a clinical pharmacist.…”
Section: Review and Feedback Strategiesmentioning
confidence: 99%